THE EFFECT OF HALF-SITTING POSITION ON PERINEAL LASERATION IN PRIMIGRAVIDA - Sri Untari; Dhiyan Nany Wigati; Nurya Kumalasari (Lppm Unan, 2023)
Background; Maternal Mortality Rate (MMR) is still a problem in Indonesia. One of the causes of MMR is bleeding. Perineal lacerations are a cause of bleeding. Allowing the mother to assume the position she desires during labor and delivery will provide many benefits, including less pain and discomfort, shorter second stage length, less perinealrupture. Method; This research used quasi experimental design with a Control Group Post test Only Design. The sampling technique used in this research is non probability sampling with purposive sampling type. The sample size used was 30 mothers giving birth. The aim of this study was to determine the effect of the half-sitting birth position on the incidence of perineal lacerations. Result; The statistical test used in this research is the Mann-Whitney Test. There were 15 women giving birth in a half-sitting position who experienced perineal lacerations, and 0 respondents who did not experience perineal lacerations. With the results obtained, the p value was 0.945 with a p value > 0.05. Conclusion; There is no influence of the half-sitting position on the incidence of perineal lacerations in primigravidas.